Diagnosis and management of coronavirus disease-associated immune thrombocytopenia: a case series - Aydın,Fatma Yılmaz (2021)
Abstract Data on health problems and fatal complications associated with coronavirus disease (COVID-19) have consistently been reported. Although immune thrombocytopenia has been associated with multiple viral infections, only few studies have shown its association with COVID-19. Here, we have reported a case series of two cases pertaining to patients diagnosed with COVID-19-associated immune thrombocytopenia, elaborating on the clinical course, management, and response to treatment.